Improving diagnostic approaches to cerebrovascular disorders in patients with hypertensive encephalopathy - Natalia Svyrydova (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Modern research today proves an increase in the incidence of ischemic stroke. Risk factors for vascular disease have become more common among young people. Clinical studies have shown that hypertension, dyslipidemia, and diabetes are traditional risk factors among the elderly. The aim of the study was to improve diagnostic approaches to cerebrovascular disorders in patients with hypertensive encephalopathy (НE) by clarifying the development of pathogenesis mechanisms, based on a comprehensive clinical study. MATERIALS AND METHODS: This qualitative study was carried by clinical and neurological examination; neuropsychological examination (Mini-Mental State Examination, abbreviated multifactorial personality questionnaire, Beck depression scale, Spielberger scale). RESULTS: The study was examined 351 patients (150 men, 201 women) with НE in hypertension of 2 degrees. The clinical examination was performed according to a two-stage method, which involves the establishment or exclusion of symptomatic hypertension. The study did not include patients with secondary hypertension, diabetes mellitus, cardiac arrhythmias, and conduction disorders, heart failure who suffered from acute cerebrovascular accident and myocardial infarction. CONCLUSION: The necessity of obligatory examination by a neurologist of patients with arterial hypertension for detection of manifestations of НE with the use of modern research methods, which allows to prevent damage to target organs, and first of all - brain damage, has been proved.